Individual differences in handedness and specific language impairment: evidence against a genetic link - D. V. M. Bishop (2001)
Data from two twin studies were used to address two related questions. First, is there any association between handedness and specific speech and language impairment (SSLI) in children? Second, is there genetic influence on individual differences in handedness, and if so, are the same genes implicated in the etiology of SSLI? The first study used data from 58 MZ and 26 DZ pairs previously recruited for an investigation into the genetic origins of SSLI. All pairs contained at least one child with SSLI. Handedness was assessed using a preference inventory, and a tapping task from which a laterality quotient (LQ) was derived. There were no handedness differences between these twins and 172 singleborn controls, and neither measure revealed any association between handedness and SSLI. The data were equally well fitted by a CE model (no genetic influence) and an AE model (no effect of shared environment), for both hand preference and tapping LQ. Nonshared environment was the largest influence on handedness for both measures. Bivariate analysis indicated no overlapping genetic influences on SSLI and handedness. In the second study handedness was assessed in a general population sample of 48 MZ and 44 DZ twin pairs aged 7 to 13 years, using a preference inventory and a pegmoving task. A subset of children was also given a test that assessed persistence of hand preference when reaching across the midline. The latter was the only measure to relate to children’s language status, with language-impaired children showing less midline crossing. This appears to reflect neurodevelopmental immaturity, rather than a stable trait. To investigate familial transmission of handedness, inventory data for parents and their twins were combined for both samples. The most parsimonious model was one that accounted for parent-child resemblance solely in terms of cultural transmission. Overall, it is concluded that there is no evidence that genes play a role in determining stable individual differences in hand preference. Insofar as there are links between handedness and speech and language difficulties these reflect delayed neuromotor maturation.